Oral health-related quality of life in pediatric patients under general anesthesia: A prospective study. Issue 2 (January 2017) - Li, Lanlan; Wang, Hongwei; Han, Xueping
Abstract : Abstract: Our goal was to evaluate how dental treatments under general anesthesia (GA) affect the quality of life by a prospective pair-matched design. Pediatric patients, who had received dental treatments under GA, were enrolled and were asked to complete the Early Childhood Oral Health Impact Scale (ECOHIS) before the treatment and 1 month after the treatment. To shield the observed impacts, a pair-matched control group was performed. Patients in the control group were also required to complete the ECOHIS at these different points in time. In both groups, the items of troubled sleep and oral/dental pain scored highest, whereas avoiding smiling or laughing and avoiding talking scored lowest before the treatment. The total mean score in the 2 groups was 13.1 and 13.7, respectively, and there was no significant statistical difference ( P  > 0.05). However, the total mean score was 1.9 in the experimental group after the treatment and smaller compared with the control group (1.9 vs. 4.7, P  < 0.001). The majority of the items in both groups had an apparent effect size and the total mean effect in the experimental group was greater than that in the control group (85.5% vs. 65.7%, P  < 0.001). Therefore, dental treatment under GA could provide better quality of life restoration compared with treatment over multiple visits.